Dignity in a digital age : making tech work for all of us - Khanna, Ro (Simon & Schuster, 2022)
"Rep Ro Khanna offers a revolutionary roadmap to facing America's digital divide. In Khanna's vision, "just as people can move to technology, technology can move to people. People need not be compelled to move from one place to another to reap the benefits offered by technological progress" (from the foreword by Amartya Sen, Nobel Laureate in Economics)"--
Includes bibliographical references (pages 291-342) and index.
osc 13/04/23
Keywords: Information economy; Information technology; Information technology; Economic development; Digital divide; Equality